Bye-Bye Barack: dislocating Afropolitanism, spectral Marxism and dialectical disillusionment in two Obama-era novels. Issue 1 (2nd April 2020) - Masterson, John
ABSTRACT: In contextually specific and formally distinctive ways, Chimamanda Ngozi Adichie's Americanah and Imbolo Mbue's Behold the Dreamers are fictional interrogations of Obama's presidential pledge to resuscitate the American dream on the wake of the global financial crash. This paper explores how they supplement and challenge familiar tropes associated with African and American, rather than African-American, diaspora writing. Given broader debates within transnational literary studies about flows and exchanges (of people, finance, cultural production, dissemination, consumption et al.) linking the global South and North, I consider how these texts grapple with the complexities and complicities of contemporary neoliberalism through the lens of renascent African Marxisms. While my chosen writers could not be described as Marxist, I engage with more materially oriented scholarship, such as Krishnan's Writing Spatiality in West Africa and Ngugi's The Rise of the African Novel, to consider how Americanah and Behold the Dreamers circulate in a global literary marketplace where certain texts, not to mention authors, are seen as symptomatic of an African and/or Afropolitan and/or 'Africapitalist' renaissance. By grappling with Marxist-inflected scholarship, this paper interrogates the politics, as well as poetics, of the oft-conspicuous airbrushing of those socio-economic, specifically class concerns at the heart of these entangled debates.